BIOMONITORING OF HEAVY METALS IN THE CITY OF JELGAVA, LATVIA USING LICHEN, XANTHORIA PARIETINA - Pilecka-Ulcugaceva, Jovita; Bakute, Anda; Purmalis, Oskars; Siltumens, Kristaps; Grinfelde, Inga (International Multidisciplinary Scientific GeoConference SGEM, 2024)
In urban environments, human health is increasingly affected by air quality, particularly air pollution with particulate matter (PM), which contains various toxic chemical elements. Car traffic is one of the main sources of air pollution in urban areas, which not only raises dust from roadways but also emits micro particles from diesel engines and tire wear containing heavy metals. The aim of the study is to evaluate the ability of the lichen species Xanthoria parietina, commonly found in Latvia, to biomonitor and bioaccumulate various heavy metals (As, Cd, Cu, Cr, Mn, Ni, Pb, Zn, V), and to use this lichen to determine the risk pollution zones in the city of Jelgava. In this study, the epiphytic lichen Xanthoria parietina was used as an air pollution biomonitor to assess long-term air pollution in Jelgava. Lichen samples of Xanthoria parietina were collected on February 14, 2017. In total, 60 samples were collected from 20 monitoring points, and 3 samples from one monitoring point outside the city center of Jelgava, approximately 7 km away. The lichen samples were analyzed using ICP-OES. Analyzing the results, five pollution groups could be identified - the first group reflected parks, while the remaining groups indicated the influence of car traffic with various metal footprints. The average element content in the samples, in descending order, was Mn>Zn>Cu>Pb>Cr>V>Ni>As>Cd. Our results indicate that heavy metals come from vehicles and fossil fuel combustion processes, such as As (0.4 µg/l - 1.9 µg/l), Cr (2.1 µg/l - 13.8 µg/l), Cu (5.7 µg/l - 40.2 µg/l), Ni (1.1 µg/l - 6.8 µg/l) and V (0.9 µg/l - 10.0 µg/l).